Glucocorticoid receptors in lung cancer: new perspectives. Issue 1 (April 2016) - Taylor, Kerryn M; Ray, David W; Sommer, Paula
Abstract : Proper expression of the glucocorticoid receptor (GR) plays an essential role in the development of the lung. GR expression and signalling in the lung is manipulated by administration of synthetic glucocorticoids (Gcs) for the treatment of neonatal, childhood and adult lung diseases. In lung cancers, Gcs are also commonly used as co-treatment during chemotherapy. This review summarises the effect of Gc monotherapy and co-therapy on lung cancers in vitro, in mouse models of lung cancer, in xenograft, ex vivo and in vivo . The disparity between the effects of pre-clinical and in vivo Gc therapy is commented on in light of the recent discovery of GR as a novel tumour suppressor gene.